«Release from criminal liability in connection with reconciliation with the victim under the new Criminal code of the Republic of Kazakhstan» (Journal of actual problems of jurisprudence, 2018)
This article considers the norm of release from criminal liability in connection with reconciliation with the victim. The comparative analysis of norms of release from criminal liability in connection with reconciliation with the victim under the new Criminal code of RK of 2014 and to the Criminal code of RK of 1997 is carried out. The bases and conditions under which the person who made a criminal offense can be exempted from criminal liability in connection with reconciliation with the victim reveal. In the article the author pays attention to a legal regulation of an order of release from criminal liability according to Art. 68 under the new Criminal code of RK of 2014. Also the author notes the positive moments of Art. 68 of the new Criminal code of RK.Key words: release from criminal liability, basis and condition of release from criminal liability, a legal regulation of an order of release from criminal liability, reconciliation with the victim, incentive norms of criminal law.